Surface Plasmon Resonances in Silver Nanostars - Faustino Reyes Gómez; Rafael J. G. Rubira; Sabrina A. Camacho; Cibely S. Martin; Robson R. da Silva; Carlos J. L. Constantino; Priscila Alessio; Osvaldo N. Oliveira; J. Ricardo Mejía-Salazar (Sensors, 2018)
The recent development of silver nanostars (Ag-NSs) is promising for improved surface-enhanced sensing and spectroscopy, which may be further exploited if the mechanisms behind the excitation of localized surface plasmon resonances (LSPRs) are identified. Here, we show that LSPRs in Ag-NSs can be obtained with finite-difference time-domain (FDTD) calculations by considering the nanostars as combination of crossed nanorods (Ag-NRs). In particular, we demonstrate that an apparent tail at large wavelengths ( <semantics> λ ≳ 700 </semantics> nm) observed in the extinction spectra of Ag-NSs is due to a strong dipolar plasmon resonance, with no need to invoke heterogeneity (different number of arms) effects as is normally done in the literature. Our description also indicates a way to tune the strongest LSPR at desired wavelengths, which is useful for sensing applications.